Distribusi Bakteri Penghasil Enzim Ekstraseluler Pada Saluran Pencernaan Lobster Mutiara (Panulirus ornatus) - Fatur rahman; Ismiati Ismiati; Arbai Nurhasanah (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2019)
The activity of the digestive function of animals is influenced by the secretion of extracellular enzymes from bacteria in the digestive tract. This study aims to evaluate the distribution of bacteria producing protease enzyme, amylase and lipase from the digestive tract of pearl lobster, Panulirus ornatus. Bacterial isolates that have extracellular enzyme activity are based on their ability to form clear zones in the test media. The results showed that of 51 bacterial isolates from the digestive tract of P. ornatus, proteolytic bacteria were 27.45%, amylolytic bacteria were 23.53% and lipolytic bacteria were 21.77%. Based on bacterial dominance in the gastrointestinal segment, namely the cardiac, piloric and intestinal sections, it was dominated by amylolytic bacteria at 33.33%, proteolytic at 37.50% and lipolytic at 29.41%. The activity of proteolytic, amylolytic and lipolytic bacteria based on the highest clear zone diameter was achieved respectively by SP5 isolates of 12 mm, SK10 isolates of 21 mm and SU15 isolates of 20 mm. The three bacterial isolates were potential as probiotic aquacultur candidates